The Effect of Price and Service Quality on Repeat Purchases and Implications for Customer Loyalty - Aloysius Ray Julian Kusdiantoro; Rahayu Puji Suci; Survival (Optima Science, 2024)
This study attempts to test a model developed to explain the effect of price and service quality on repeat purchases and its implications on customer loyalty at PT. Global Jet Express. The research method used is descriptive quantitative with the population of all consumers who have used the services of PT. Global Jet Express and sample determination in this study based on the opinion of Ferdinand (2006) suggest that the sample size depends on the number of indicators used in all variables multiplied by 5 to 10. The sample obtained amounted to 90 with the characteristics of consumers who at least made two purchases. The analytical techniques in this study used descriptive and inferential statistical analysis techniques. The results showed that the appropriate price could not increase customer loyalty. Good service quality cannot increase customer loyalty. An appropriate price can increase repeat purchases. Good quality service can increase repeat purchases. Repurchases can increase customer loyalty. Appropriate pricing can affect customer loyalty mediated by repeat purchases. Good service quality can affect customer loyalty mediated by repeat purchases.